The knowledge domain of cognitive neuroscience of aging: A Scientometric and bibliometric analysis - Jiang, Jiaxing; Fan, Lin; Liu, Jia (Frontiers in Aging Neuroscience, 2023)
Cognitive neuroscience of aging (CNA) is a relatively young field compared with other branches of cognitive aging (CA). From the beginning of this century, scholars in CNA have contributed many valuable research to explain the cognitive ability decline in aging brains in terms of functional changes, neuromechanism, and neurodegenerative diseases. However, very few studies have systematically reviewed the research in the domain of CAN, with regard to its primary research topics, theories, findings, and future development. Therefore, this study used CiteSpace to conduct a bibliometric analysis of 1,462 published articles in CNA from Web of Science (WOS) and investigated the highly influential and potential research topics and theories of CNA, as well as important brain areas involved in CAN during 2000–2021. The results revealed that: (1) the research topics of “memory” and “attention” have been the focus of most studies, progressing into a fMRI-oriented stage; (2) the scaffolding theory and hemispheric asymmetry reduction in older adults model hold a key status in CNA, characterizing aging as a dynamic process and presenting compensatory relationships between different brain areas; and (3) age-related changes always occur in temporal (especially the hippocampus), parietal, and frontal lobes and the cognitive declines establish the compensation relationship between the anterior and posterior regions.